Planiranje nastave engleskog jezika (Philologia, 2021)
The ﬁrst two parts of this paper focus on the purpose and complexity of long- and short-term planning activities in ELT. They clearly state the existence of planning processes at all levels and stages of pedagogic hierarchy – from curriculum design to single lesson planning. The numerous factors which affect these processes are listed in order to be taken into account during lesson-planning.The aim of the last part of the paper is to introduce one of many possible ways to classify plans, in this case according to their main purpose and the teaching period they cover. Some of the problems related to the subject, including everyday course- and lesson-planning dilemmas, are discussed as well. Finally, this paper emphasizes the importance of planning to all English teachers regardless of their professional background.